2006
DOI: 10.1097/00054725-200606000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of experimental mouse colitis and association with inflammatory activity

Abstract: Our results show that MRI can be used to depict healthy and inflamed mouse colon and that the T2w signal, contrast-enhanced T1w signal, and colon wall thickness may be used to characterize inflammation in experimental colitis. These potential biomarkers may be useful in the evaluation of putative drugs in longitudinal studies in both mice and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…The colon wall was macroscopically scored for the following parameters: thickness (0-4), stiffness (0-2), oedema (0-3) and visible ulcerations (0-1), with a total maximum score of 10 as previously described [8].…”
Section: Methodsmentioning
confidence: 99%
“…The colon wall was macroscopically scored for the following parameters: thickness (0-4), stiffness (0-2), oedema (0-3) and visible ulcerations (0-1), with a total maximum score of 10 as previously described [8].…”
Section: Methodsmentioning
confidence: 99%
“…Intestinal inflammation usually leads to an accumulation of inflammatory cells in the intestinal mucosa, leading to a thicker intestinal wall. The thinner intestinal wall observed when using antibiotics as feed additives is consistent with a reduction in inflammation because of the reduced influx and accumulation of inflammatory cells (LARSSON et al, 2006). Moreover, inflammation and cytokine release promotes catabolism of muscle tissue and loss of appetite (GRUYS et al, 2006), which additionally affects an animal's performance.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, a strong correlation has been reported between colonic inflammatory severity and colon wall thickness in an animal model of colitis. 10) Melgar et al showed that histological inflammatory score in colonic mucosa and colon weight per unit length progressively increased after cessation of DSS treatment. 9) Taken together, the present and previous findings suggest that the colon weight per unit length may be useful as a comprehensive and objective indicator of colonic inflammatory responses such as immune cell infiltration of mucosal and submucosal regions, mucosal edema, epithelium hyperplasia, collagen deposition, and fibrosis.…”
Section: Discussionmentioning
confidence: 99%